Macrophage Populations and Expression of Regulatory Inflammatory Factors in Hepatic Macrophage-depleted Rat Livers under Lipopolysaccharide (LPS) Treatment. (July 2018) - Pervin, Munmun; Karim, Mohammad Rabiul; Kuramochi, Mizuki; Izawa, Takeshi; Kuwamura, Mitsuru; Yamate, Jyoji
To investigate the significance of the appearance of hepatic macrophages and expression of inflammatory factors in normal and macrophage-depleted livers, hepatic macrophages were depleted with liposome (Lipo)-encapsulated clodronate (CLD; 50 mg/kg, i.v.) followed by lipopolysaccharide (LPS) administration (0.1 mg/kg, i.p.) in F344 rats (CLD + LPS). Vehicle control rats (Lipo + LPS) received empty-Lipo before LPS. The low dose of LPS did not result in microscopic changes in the liver in either treatment group but did modulate M1 and M2 macrophage activity in Lipo + LPS rats without altering repopulating hepatic macrophages in CLD + LPS rats. LPS treatment in Lipo + LPS rats dramatically increased the M1 (IL-1β, IL-6, TNF-α, and MCP-1) but not M2 macrophage-related factors (IL-4 and CSF-1) compared to CLD + LPS rats. In the CLD + LPS rats, the M2 macrophage-related factors IL-4 and CSF-1 were elevated. In conclusion, low-dose LPS activated hepatic macrophages in rat livers without causing liver injury or stimulating repopulating hepatic macrophages. These data suggest that LPS may alter the liver microenvironment by modulating M1 or M2 macrophage-related inflammatory mediators and macrophage-based hepatotoxicity.